Effects of cardiac resynchronisation therapy on dilated cardiomyopathy with isolated ventricular non-compaction. Issue 4 (16th December 2010) - Bertini, Matteo; Ziacchi, Matteo; Biffi, Mauro; Biagini, Elena; Rocchi, Guido; Martignani, Cristian; Ferlito, Marinella; Pasquale, Ferdinando; Cervi, Elena; Branzi, Angelo; Rapezzi, Claudio; Boriani, Giuseppe
Abstract : Objective: To compare the effects of cardiac resynchronisation therapy (CRT) on left ventricular (LV) reverse remodelling in patients with dilated cardiomyopathy (DCM) associated or not with isolated ventricular non-compaction (IVNC). Methods and results: 52 patients with heart failure, candidates for CRT, were recruited: 20 patients with IVNC associated with DCM (IVNC-DCM) without other coexisting cardiac diseases and 32 patients with DCM without IVNC matched for age, gender, body surface area and LV systolic function. Standard and contrast echocardiography were used to assess LV volumes and function and to optimise visualisation of the endocardial border at baseline and at 6 months' follow-up. Patients with heart failure were subsequently classified as CRT negative responders, non-responders, responders or super-responders based on different LV reverse remodelling 6 months after CRT implantation. Different types of CRT response were observed in IVNC-DCM and DCM patients. In particular, in IVNC-DCM patients the percentage of super-responders was significantly higher than for patients with DCM (60% vs 28%, respectively, p=0.023). In addition, the number of IVNC segments had a trend towards reduction with respect to baseline (4 (3–6)) at 6 months' follow-up (3 (1–5); p=0.067). Finally, in IVNC-DCM, the patients with a higher number of IVNC segments at baseline (>4) were more likely to be responders or super-responders than patients with ≤4 IVNC segments (p=0.003). Conclusions: Patients with IVNC-DCM had greater LV reverse remodelling after CRT than patients with DCM. The greater the area of non-compaction (higher number of IVNC segments) the greater the chance of achieving CRT response and greater LV reverse remodelling.